Some electrical properties of PVA:PEG/MnCl2 thin film composites - Suhail, Mahdi Hasan (Iraqi Journal of Physics, 2019)
PVA:PEG/MnCl2 composites have been prepared by adding (MnCl2) to the mixture of the poly vinyl alcohol (PVA) and poly ethylene glycol (PEG) with different weight percentages (0, 2, 4, 6, 8 and 10) wt.% by using casting method. The type of charge carriers, concentration (nH) and Hall mobility (μH) have been estimated from Hall measurements and show that the films of all concentration have a negative Hall coefficient. In D.C measurement increase temperature leads to decrease the electrical resistance. The D.C conductivity of the composites increases with the increasing of the concentration of additive particles and temperature. The activation energy decreases for all composites with increasing the concentration of the additive particles. The A.C conductivity increases with increasing of the frequency and the concentration of MnCl2 particles. The A.C electrical properties show that the dielectric constant and dielectric loss of the composites decrease with increasing of the frequency.